Determining Glomerular and Non-Glomerular Hematuria Dysmorphic Red Blood Cell: Study on Automatic Urine Analyzer - Dias Setiawan; B. Rina A. Sidharta; Dian Ariningrum (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Hematuria is a sign of glomerular and non-glomerular kidney disease. Erythrocytes that pass through the glomerulus will change shape to become dysmorphic. Dysmorphic red blood cells (dRBC) can be screened using an automatic urine analyzer based on flowcytometry to distinguish the source of hematuria from glomerular or non-glomerular. The purpose of this study was to determine the diagnostic performance of the flowcytometry-based dRBC automatic urine analyzer in differentiating glomerular and non-glomerular hematuria. This study used a cross-sectional research design at the Clinical Pathology Installation at RSUD Dr. Moewardi in Surakarta. The subjects of the study were patients with hematuria at the Polyclinic and Internal Medicine Ward, Nephrology sub-division, Pediatric Polyclinic, nephrology sub-division, Urology Surgery Polyclinic in March – July 2021. The diagnostic test was carried out after determining the cut-off value of dRBC with ROC curve and AUC value. The results showed that the cut-off value of dRBC for glomerular and non-glomerular hematuria was 67% and had the best analytical performance with sensitivity 91.07%, specificity 85.36%, AUC 0.890 (95%CI: 0.832–0.947; p=0.000). In this study, dRBC parameters can be used for screening and diagnostics of patients with glomerular and non-glomerular hematuria. Further research needs to be done with other more specific gold standards such as examination of urine sediment with a phase contrast microscope.